Characterization and optimization of production of bacterial cellulose from strain CGMCC 17276 based on whole-genome analysis. (15th March 2020) - Lu, Tingfen; Gao, Hongliang; Liao, Bowen; Wu, Jiajing; Zhang, Wei; Huang, Jie; Liu, Mingyao; Huang, Jing; Chang, Zhongyi; Jin, Mingfei; Yi, Zhengfang; Jiang, Deming
Highlights: Strain CGMCC 17276 is a high-yield BC-producing novel species of Komagataeibacter . bcs II and bcs III operon showed high transcriptional expression under static and agitated conditions. The highest yield of BC production reached using glycerol as single carbon source. Waste glycerol was successfully used as a sustainable strategy for BC production. Abstract: Bacterial cellulose (BC) has received considerable attention as an environment-friendly, biodegradable nanomaterial. In this study, the strain Komagataeibacter sp. nov. CGMCC 17276, which showed rapid cell growth and high BC-production ability, was isolated and classified into a novel species in the Komagataeibacter genus. Four BC synthase operons were annotated using whole-genome analysis, partially explaining the high BC yield of strain CGMCC 17276. Operons bcs Ⅱ and bcs Ⅲ showed high transcriptional levels under static and agitated culture conditions, indicating their importance in BC synthesis. Of the eight suitable carbon sources identified by whole-genome analysis, the highest BC production was achieved using glycerol as a single carbon source. Finally, waste glycerol was successfully used as an eco-friendly and sustainable strategy for BC production. This study provides valuable insights into the mechanism of BC synthesis, genetic structure of BC-producing strains, and industrialization of BC production using an eco-friendly and low-cost strategy.